Specific Hygiene Procedures and Practices Assessment: A Cross-Sectional Study in Fresh Fishery Product Retailers of Lisbon’s Traditional Food Markets - Rafael Sousa Oliveira; Maria José Rodrigues; Ana Rita Henriques (Foods, 2021)
This study aimed to assess the compliance of specific hand hygiene and food contact surfaces hygiene in fresh fishery product retailers (FFPR) and its relation to socio-demographic characteristics that might influence the observed procedures and practices. A cross-sectional study was conducted in traditional food markets’ FFPRs (N = 74) using interviews and audits for data collection purposes. Results revealed that women were overrepresented among FFPR managers; most were over 50 years of age and had a long working experience in fish retail activities, despite a low educational level. The majority had attended training courses in food hygiene, safety, and Hazard Analysis and Critical Control Points-based procedures. Both documental assessment and hand hygiene procedures and practices verification revealed a low level of compliance. Many documents supporting hygiene practices were lacking. Several non-conforming requisites were identified related to the handwashing procedure and equipment and to glove wearing practices. A higher level of compliance was obtained in food contact surfaces hygiene procedures and practices verification, with complete hygiene procedures applied and proper cleaning of utensils and chemical products management in several cases. These findings reflect an ambiguous understanding and misconceptions related to hygiene procedures and practices, suggesting the need to improve and update FFPR food handler training regarding basic food hygiene and safety.